All-optical probe of sub-THz spin precession in a L10 MnGa nanolayer. (25th March 2019) - Mizukami, Shigemi; Suzuki, Kazuya Z.; Miura, Yoshio
Abstract: We measured an all-optical time-resolved magneto-optical Kerr effect for L 10 MnGa ultrathin films fabricated with a low-temperature hetero-epitaxy technique. Spin precession was observed with a frequency over 0.1 THz due to a large perpendicular magnetic anisotropy (PMA) field of ∼3 T. The effective Gilbert damping constant α eff was sensitive to the deposition temperature. A minimum value of α eff of 0.017 was observed, which was about twice as large as that reported for much thicker films of MnGa with high chemical ordering but was comparable to those reported in other nanometer-thick PMA material films.